Very high gravity sucrose fermentation by Brazilian industrial yeast strains: effect of nitrogen supplementation - Betite, Vivia Cristina [UNESP]; Miranda Junior, Messias [UNESP]; Oliveira, Jose Eduardo de [UNESP]; Ernandes, Jose Roberto [UNESP] (Inst Brewing, 2012)
In this study three industrial strains were inoculated into natural sugar cane juice containing 22, 30 and 35% (w/v) sucrose supplemented with nitrogen sources with differing structural complexities, which varied from a single ammonium salt (ammonium sulphate) to peptides (peptone), under aerobic and anaerobic conditions. At 30 degrees C, in shaken cultures, it was found that efficient sucrose utilization occurred only in media supplemented with a nitrogen source. In general, under agitation, supplementation with peptone led to more efficient fermentation compared with ammonium sulphate supplementation, with higher biomass accumulation and maintenance of cell viability. In a 35% (w/v) sucrose fermentation, under conditions with an inoculation of low cell density, nitrogen supplementation was required to obtain complete sucrose utilization, suggesting the possibility of producing wines with higher amounts of ethanol under working conditions that approach the limit of yeast alcohol tolerance. The results in this study have industrial relevance and they indicate that, under appropriate environmental and nutritional conditions, the commercial Brazilian yeast strains studied can efficiently use sugar, with high cell viability, even during very high gravity sucrose fermentation conditions. Copyright (c) 2012 The Institute of Brewing & Distilling
Keywords: amino acids; anaerobiosis; ethanol production strain; nitrogen metabolism; peptides; Saccharomyces; sucrose fermentation